Literasi Digital: Meningkatkan Kesadaran Keamanan Internet di Kalangan Siswa SMP - Fathir; Alamin, Zumhur; Amirul Mu'min, Muhammad; Ilmih, Muhammad (SEWAGATI: Jurnal Pengabdian kepada Masyarakat, 2024)
The growing functionality of the internet makes it accessible to all. Recently, several studies have shown that most internet users are teenagers. The development of social media worldwide indirectly has a big influence on internet usage for teenagers. The focus of this service is to increase internet safety awareness among junior high school students, in terms of several aspects and activity patterns of using social media in adolescents. sufficient knowledge of things that should be done and not related to safety in using social media The research was conducted to students of SMPN 9 SATAP which is in Wora village, Wera District. The results showed that SMPN 9 SATAP students in general were able to determine the use of the internet properly, both for learning facilities and entertainment functions such as social media, where student interaction time in direct interaction in daily life and interaction time on social media was balanced and in accordance with their portions. It can also be seen that the students of SMPN 9 SATAP have not been able to know about the basics of computer recognition, such as the functions of the keyboard keys.